Sofosbuvir and Velpatasvir combination is safe and effective in treating chronic hepatitis C in end‐stage renal disease on maintenance haemodialysis. (17th March 2021) - Taneja, Sunil; Duseja, Ajay; Mehta, Manu; De, Arka; Verma, Nipun; Premkumar, Madhumita; Dhiman, Radha K.; Singh, Virendra; Singh, Mini P.; Ratho, Radha K.; Ramachandran, Raja; Kumar, Vivek; et al.
Abstract: Background & Aims: There is emerging data on the use of Sofosbuvir‐based directly acting antiviral (DAA) drug regimens in chronic hepatitis C (CHC) patients with end‐stage renal disease (ESRD) on maintenance haemodialysis (MHD). We evaluated the safety and efficacy of Sofosbuvir plus Velpatasvir fixed‐dose combination in CHC patients with ESRD on MHD. Methods: Fifty‐one CHC patients with ESRD on MHD were included in a real‐life prospective study. All patients irrespective of genotype; presence of cirrhosis; treatment naive or experienced status were treated with full‐dose Sofosbuvir (400 mg) plus Velpatasvir (100 mg) fixed‐dosed combination given daily for 12 weeks. The efficacy was assessed by the sustained virological response (SVR12) with negative HCV RNA 12 weeks after the end of treatment (ETR). Side effects if any were recorded in all patients. Results: The median HCV RNA level in 51 CHC patients [Males 41 (80.4%), mean age 42.8 ± 14.6 years] was 2.0 × 10 6 IU/mL. HCV genotype was available in 19 patients with predominant genotype 1 in 15 (79%) patients. Ten (19.6%) patients had evidence of cirrhosis (defined as LSM ≥ 12.5 kPa on Transient Elastography), and 8 (15.6%) patients were treatment experienced. Testing for ETR was done in 36 patients and all 36 (100%) patients achieved ETR, and 49 patients (96%) achieved SVR 12. All 51 patients tolerated the Sofosbuvir + Velpatasvir combination, with none of the patients reporting any serious adverse event. Conclusion: Sofosbuvir plus Velpatasvir fixed‐dose combination is safe and effective in treating CHC in patients with ESRD on MHD.